(untitled) (Journal of Mechanical Engineering, 2016)
High level surface finish (SF) achievement is one of the major advantages of conventional investment casting process. Not much work hitherto has been reported for modeling the SF in conventional investment casting of industrial components. In the present study application of dimensionless analysis, has been made for developing a mathematical model for SF. Three input process parameters (namely: molten metal pouring temperature (PT), slurry layers combination (LC) and volume/surface-area (V/A) ratio of cast components) were judicially selected to give SF as output. This study provide main effects of these input parameters on SF and shed light on the SF mechanism in conventional investment casting. The comparison of mathematical model with experimental results has been made for validation of model.